Optimization of the rotor of a magnetoelectric synchronous machine with pole tips shaped as elliptical arcs - V. V. Kharlamov; Yu. V. Moskalev; A. Yu. Milyutin (Омский научный вестник)
The article optimizes the rotor of a synchronous machine with tangentially magnetized magnets. The rotor pole tips have a shape resembling an arc of an ellipse. The simulation of the magnetic circuit of a synchronous machine is performed using the FEMM program. The optimization problem is solved using the coordinateby-coordinate descent method; for each coordinate axis, the minimum value of the objective function is determined by the dichotomy method. Permissible ranges of variation for the variable values, which define the dimensions of the rotor's structural elements, are considered as segment boundaries within the dichotomy method for each coordinate axis. The optimal size values of the permanent magnets and pole tips on the rotor, shaped as an elliptical arc for a four-pole machine, are calculated. The curves of the normal component of magnetic induction in the air gap of a synchronous machine with pole tips shaped as both a circular arc and an elliptical arc are compared. A mock-up of a four-pole electric machine with permanent magnets on the rotor is constructed, and the electromotive force curves of the stator winding at idle are obtained.